2003
DOI: 10.1007/s00592-003-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and respiratory function

Abstract: Although the effects of sex, ageing, height, race, and current and past health on pulmonary function tests have been described, only non-significant associations have been observed between body weight and lung function among healthy persons after having accounted for the effects of age and height. However, few studies have considered the influence of body compartments (e. g. lean and fat masses and their distribution) on lung function and respiratory gas exchange. The present work consists of a review of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 49 publications
5
28
1
5
Order By: Relevance
“…Anthropometric and body composition variables showed correlation with the PEF, corroborating with the results of several other studies [9,16,19,30,31]. The results of our research elucidated that maternal age and height were positively related to the PEF in primigravidae.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Anthropometric and body composition variables showed correlation with the PEF, corroborating with the results of several other studies [9,16,19,30,31]. The results of our research elucidated that maternal age and height were positively related to the PEF in primigravidae.…”
Section: Discussionsupporting
confidence: 92%
“…In view of the factors that can influence the PEF such as sex, age, height, race and BMI [9,[16][17][18]. It is noted the importance of monitoring changes in pregnancy weight, since the progressive changes in the form and abdomen configuration, diaphragm and ribcage, besides increasing the size of the uterus and fetal growth could compromise pulmonary function during gestation [9,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…The change in the measured V TG was signifi- This association between WC changes and measured V TG changes might be explained by a variety of mechanisms. Abdominal fat deposition may directly impede the descent of the diaphragm into the abdominal cavity, whereas fat deposition in the chest wall may diminish rib cage movement and thoracic compliance, both of which lead to restrictive respiration impairment (Maiolo et al, 2003). Other mechanisms have been suggested, including the possibility that abdominal fat deposition leads to a redistribution of blood to the thoracic compartment that reduces vital capacity (Harik-Khan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted in obese people, it has been suggested that the decrease in the chest wall compliance may be caused by adipose tissue around the abdomen (12). The effects of obesity was determined as reduction in functional residual capacity and expiratory reserve volume and increase in residual volume (13).…”
Section: Discussionmentioning
confidence: 99%